2020
DOI: 10.5946/ce.2020.127
|View full text |Cite
|
Sign up to set email alerts
|

A New Active Locomotion Capsule Endoscopy under Magnetic Control and Automated Reading Program

Abstract: Capsule endoscopy (CE) is the first-line diagnostic modality for detecting small bowel lesions. CE is non-invasive and does not require sedation, but its movements cannot be controlled, it requires a long time for interpretation, and it has lower image quality compared to wired endoscopy. With the rapid advancement of technology, several methods to solve these problems have been developed. This article describes the ongoing developments regarding external CE locomotion using magnetic force, artificial intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…With the emergence of CE in 2000[ 17 ], it has revolutionized our understanding of small intestinal mucosa[ 18 - 20 ], enabling doctors to detect small intestinal mucosal erosion, ulcers, vascular disease, bleeding, polyps, parasite and other lesions more efficiently. However, reliable and rapid reading of video is still a challenge, but more and more studies have shown that the combination of AI and CE can greatly improve the efficiency of our evaluation of small intestinal mucosal lesions; the detection accuracy was above 90% in most studies[ 21 - 27 ].…”
Section: Ai In Small Intestine Anatomymentioning
confidence: 99%
“…With the emergence of CE in 2000[ 17 ], it has revolutionized our understanding of small intestinal mucosa[ 18 - 20 ], enabling doctors to detect small intestinal mucosal erosion, ulcers, vascular disease, bleeding, polyps, parasite and other lesions more efficiently. However, reliable and rapid reading of video is still a challenge, but more and more studies have shown that the combination of AI and CE can greatly improve the efficiency of our evaluation of small intestinal mucosal lesions; the detection accuracy was above 90% in most studies[ 21 - 27 ].…”
Section: Ai In Small Intestine Anatomymentioning
confidence: 99%
“…Since 2010, deep learning and convolutional neural network (CNN) algorithms have been used in medicine. Currently, the CNN algorithm is being used as the dominant AI algorithm in the field of medical image reading [ 13 ]. As previously mentioned, it takes a lot of time and effort to read a capsule endoscopy.…”
Section: Application Of Artificial Intelligence (Ai) Into the Reading Of Small Bowel Capsule Endoscopy (Sbce)mentioning
confidence: 99%
“…However, these reading tools have a limitation in that they are less accurate than conventional reading [ 11 , 12 ]. Currently, lesion detection using an AI algorithm has emerged as a way to save reading time while maintaining the accuracy of lesion detection compared to conventional reading [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most other in-building magnetic-controlled capsule endoscopy systems developed in recent decades [ 5 , 6 , 7 , 8 ], the IMS MACE system is highly portable and thus provides a solution for physicians to perform upper GI endoscopy for patients outside hospital or clinic settings. It is known that peptic ulcer disease and esophageal reflux are common in the senior population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%